ADDRESSING FOOD SECURITY ISSUES USING A HUMAN RIGHTS-BASED APPROACH - Pineda-Ofreneo, Rosalinda (Philippine Journal of Social Development; Vol 5 (2013): Philippine Journal of Social Development, 2014)
-